Perancangan dan Pembuatan Sistem Informasi Perpustakaan Pada SMA Negeri 1 Dolok Pardamean - Edy Budi Harjono Sibarani (Jurnal Multidisiplin Indonesia, 2025)
The library is a school facility for managing the provision of textbooks and accompanying books related to general science, technology and other applied sciences. The library system at SMA Negeri 1 Dolok Pardamean is still not computerized, data management is still carried out using master book records. For this reason, a computerized system or computer application program is needed that can speed up and simplify the data processing process from the library at SMA Negeri 1 Dolok Pardamean. Research on designing a web-based library information system at SMA Negeri 1 Dolok Pardamean was carried out using the Software Development Life Cycle (SDLC) method. ) with a waterfall model. The web-based school library information system at SMA Negeri 1 Dolok Pardamean was developed using the CodeIgniter4 framework with the PHP programming language and MYSQL database. Based on the Alpha test results (black box and white box testing) it can be concluded that all test results are good and the Alpha test was successful. Furthermore, based on the results of beta testing in validation, experts obtained a percentage score of 89.5% with the statement strongly agree and the average value of the user questionnaire assessment was 86.64% with the statement strongly agree. Based on the results of the research and testing above, it can be concluded that the web-based library information system at SMA Negeri 1 Dolok Pardamean which was designed is a functional requirement which is expected to make it easier for library staff to manage and input book data.